Suppression of haematopoiesis during therapy of chronic hepatitis C with different interferon α mono and combination therapy regimens. Issue 7 (10th June 2005) - Schmid, M; Kreil, A; Jessner, W; Homoncik, M; Datz, C; Gangl, A; Ferenci, P; Peck-Radosavljevic, M
Abstract : Background: Treatment of chronic hepatitis C with interferon (IFN)-α and ribavirin has haematotoxic effects. We evaluated the effects of four different IFN/IFN-ribavirin treatment regimens on haematopoiesis. Methods: Haematopoiesis was studied in 133 patients with chronic hepatitis C receiving IFN-α2b alone (group A) or in combination with ribavirin (group B), pegylated IFN-α2a (group C), or pegylated IFN-α2b (group D) in combination with ribavirin. Results: At week 4, haemoglobin levels were diminished in all groups receiving combination therapy. In the monotherapy group, haemoglobin decreased slightly after eight weeks. In all groups, haemoglobin remained diminished throughout therapy. In all patients, leucocytes (while blood cells) decreased after four weeks and remained low during treatment. Platelets (peripheral platelet count (PPC)) were decreased in all groups after four weeks and remained below baseline levels during therapy in group A, C, and D whereas in group B PPC recovered early and reached baseline levels at week 16 of therapy. Concomitantly with the decreases in haemoglobin and PPC, erythropoietin increased in all groups receiving combination therapy and thrombopoietin in all groups. Patients treated with pegylated IFN-α2a and those who received pegylated IFN-α2b combination therapy differed only in leucopoiesis, whereas erythropoiesis and thrombopoiesis were comparable. Conclusion: IFN-α based therapies are associated with a decrease in all three haematopoietic lineages, irrespective of the type of therapy used. The stronger suppressive effect of pegylated IFN-α2a on leucopoiesis could be due to a dose effect. Overall, concentrations of endogenous haematopoietic growth factors are increased but can only partially alleviate haematotoxicity. Potential uses of exogenous haematopoietic growth factors and their impact on the virological response need to be explored.